The Cladocera (Crustacea: Branchiopoda) of six high altitude water bodies in the North Chilean Andes, with discussion of Andean endemism - Kotov, Alexey A.; Sinev, Artem Y.; Berrios, Viviana Lorena (Zootaxa, 2010)
It was recently demonstrated that mountain areas add to a significant increase of the number of known cladoceran species due to higher chances of endemism. We studied six water bodies in the North Chilean Andes (XV, I and II Regions of Chile), located at more than 4000 m above sea level, and found 19 species of the Cladocera. Several selected taxa are redescribed in detail. Three new species are described: Daphnia (Ctenodaphnia) paggii sp. nov. from Salar de Lagunillas, Pleuroxus fryeri sp. nov. from Crater Lake in Licancabur Volcano (type locality) and Laguna Leija, Alona altiplana sp. nov. from Crater Lake in Licancabur Volcano (type locality) and three other water bodies. A single female, determined as Coronatella cf. circumfimbriata (Megard, 1967) from Salar de Lagunillas, probably also belongs to a yet undescribed species. Geoffreya fryeri gen. nov., sp. nov. is found in a single locality, Salar de Lagunillas. The genus Geoffreya gen. nov. (Chydoridae: Aloninae) is different from all other genera of Aloninae in a set of unique and rare characters, such as (1) exopodites III and IV, both having only four setae, all of them terminal, (2) seta 1 of exopodite V longer than setae 2–4, (3) six setae in filter plate II; (4) small size of exopodites III–V in comparison with limb I; (5) two interconnected main head pores of different size; (6) clusters of hard setules on basal and middle segments of antenna II exopodite, (7) very long setules in the lateral fascicles on the postabdomen. The postabdominal claw in Geoffreya gen. nov. bears a very short basal spine. Among 19 species found, four taxa can be regarded as cosmopolitan, ten (more than half among 19!) are Andean endemics (among them six have Patagonian congeners), two are Andean-Patagonian, one circum-Neotropical, one “Gondwanian”, one found in two very distant localities, in the Andes and high mountains of Mexico. Some zoogeographical patterns revealed in this study are discussed. Some species groups, i.e. Daphnia paggii sp. nov. and its conge-4 · Zootaxa 2430 © 2010 Magnolia Pressners, Ilyocryptus nevadensis and its congeners, are probably differentiated from some pan-continental Mesozoic taxa. We agree with previous authors that the Andean-Patagonian patterns in the cladoceran distribution likely has a Last Glacial Maximum (LGM) signature (Löffler 1984; Adamowicz et al. 2002; Mergeay et al. 2008). Based on the marked increase of number of endemic Andean taxa after our investigation of only six water bodies, we assume that the number of Neotropical endemics in the Cladocera could be significantly increased in course of further studies of the Andean high altitude waters.